Photochemically-Activated p-Type CuGaO2 Thin Films for Highly-Stable Room-Temperature Gas Sensors. Issue 3 (1st March 2023) - Lin, Pei-Te; Yu, Chih-Ying; Ho, Sin-Huei; Pan, Shiuan-Wei; Jhang, Jyun-Siang; Zhang, Yi-Xun; Zhang, Yo-Lun; Hsieh, Tian-Tsz; Wang, Hao-Chien; Hsueh, Wen-Jeng; Huang, Chun-Ying
Abstract : The photochemical activation process is a promising way to operate metal oxide gas sensors at room temperature. However, this technique is only used in n-type semiconductors. In this study, we report a highly stable p-type copper gallium oxide (CuGaO2 ) gas sensor fabricated through the facile sol-gel process. The sensor is capable of detecting O3 gas at room temperature, and its gas response can be further enhanced by ultraviolet (UV) activation. The highest gas response of 7.12 to 5 ppm O3 gas at a UV intensity of 10 mW cm −2 is achieved at room-temperature. In addition, the CuGaO2 sensor shows excellent long-term stability, with a degradation of approximately 3% over 90 days. These results strongly support the solution-processed CuGaO2 as a good candidate for room-temperature gas sensors.